2016
DOI: 10.1038/srep26129
|View full text |Cite
|
Sign up to set email alerts
|

Paneth Cell in Adenomas of the Distal Colorectum Is Inversely Associated with Synchronous Advanced Adenoma and Carcinoma

Abstract: Recent studies have linked appearance of Paneth cells in colorectal adenomas to adenoma burden and male gender. However, the clinical importance of Paneth cells' associations with synchronous advanced adenoma (AA) and colorectal carcinoma (CRC) is currently unclear. We performed a comprehensive case-control study using 1,900 colorectal adenomas including 785 from females, and 1,115 from males. Colorectal cancer (CRC) is the third leading cause of cancer-related deaths among both men and women in the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Furthermore, the frequency of observing Paneth cells was found to be lowest in gallbladder cancer tissues compared to non-neoplastic mucosa, suggesting an inverse correlation of PCM to gallbladder cancer (Yamamoto et al, 1989). This observation was consistent with a recent comprehensive case-control study of 1,900 colorectal adenomas showing metaplastic Paneth cells in distal colorectal adenomas were inversely associated with synchronous advanced adenoma and carcinoma (Mahon et al, 2016). Sakaki et al (2000) observed a case of gallbladder adenocarcinoma with extensive PCM.…”
Section: Appearance Of Paneth Cells In Other Gastrointestinal and Nonsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the frequency of observing Paneth cells was found to be lowest in gallbladder cancer tissues compared to non-neoplastic mucosa, suggesting an inverse correlation of PCM to gallbladder cancer (Yamamoto et al, 1989). This observation was consistent with a recent comprehensive case-control study of 1,900 colorectal adenomas showing metaplastic Paneth cells in distal colorectal adenomas were inversely associated with synchronous advanced adenoma and carcinoma (Mahon et al, 2016). Sakaki et al (2000) observed a case of gallbladder adenocarcinoma with extensive PCM.…”
Section: Appearance Of Paneth Cells In Other Gastrointestinal and Nonsupporting
confidence: 91%
“…The detection of Paneth cells in colorectal adenomas was reported as early as 1967 (Gibbs, 1967) and the reported frequencies of such detection varied from 0.2 to 39% in different studies (Bansal et al, 1984;Wada et al, 1994Wada et al, , 2005Joo et al, 2009;Pai et al, 2013;Mahon et al, 2016). Furthermore, Paneth cells not only produce antimicrobial components but also constitute an important epithelial niche for small intestinal stem cells by producing epithelial growth factor (EGF), transforming growth factor (TGF-α), Wnt3, and Notch ligands (Sato et al, 2011).…”
Section: Metaplastic Paneth Cells In Colon and Its Disease Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Moxifloxacin-based TPM would be useful for studying the interplay of small intestinal Paneth cells and mucosal immune defense system in health 3 , 41 – 43 , inflammatory bowel disease (IBD) pathogenesis 33 , 44 48 , and metabolic syndrome 49 . Perhaps, it could also be developed as a diagnostic or prognostic method including endoscopy to examine the abnormalities of Paneth cell granules in IBD animal models and human patients in vivo 33 , 45 , 46 . Therefore, TPM with moxifloxacin labeling might be useful to study Paneth cell functions and related diseases in preclinical animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Some authorities have found that PCM affects the prognosis of certain pre-neoplastic conditions and tumors. Furthermore, it was found by some investigators that the presence of PCM in distal colorectal adenoma is inversely associated with synchronous severely dysplastic adenoma or adenocarcinoma [ 9 ]. Chen et al [ 10 ] also found that the presence of PCM in cases of Barrett’s esophagitis is associated with a higher risk for disease progression.…”
Section: Discussionmentioning
confidence: 99%